Low prognostic nutritional index predicts poor outcome in newly diagnosed angioimmunoblastic T-cell lymphoma - Li, Renqin; Zhang, Wei; Yu, Le; Wu, Ping; Huang, He; Guo, Hongqiang; Lin, Tongyu; Hong, Huangming; Weng, Huawei (Frontiers in Nutrition, 2025)
BackgroundAngioimmunoblastic T-cell lymphoma (AITL) is a rare subtype of peripheral T-cell lymphoma, characterized by an aggressive disease course and poor prognosis. The prognostic nutritional index (PNI), which reflects nutritional and immune status, has emerged as a potential prognostic factor in various cancers.MethodsIn this multicenter retrospective study, a total of 173 patients with AITL between January 2010 and December 2022 were enrolled from three institutes in China. The optimal cutoff value for PNI was determined using the maximally selected rank statistics (MaxStat) analysis. The association of PNI and overall survival (OS) or progression free survival (PFS) was evaluated in univariable and multivariable Cox regression analyses. Receiver operating characteristic (ROC) curves were used to evaluate the prognostic performance and predictive accuracy of PNI combined with International Prognostic Index (IPI) and Prognostic Index for T-cell lymphoma (PIT).ResultsBased on the MaxStat analysis, a score of 40.8 was identified as the optimal cutoff value for the PNI. Survival analysis revealed that the low PNI group had worse OS and PFS. The 3-year OS and PFS for the low PNI group were 27.5 and 26.5%, respectively, compared to 84.7 and 74.4% for the high PNI group (p < 0.001). Multivariate analyses indicated that PNI was significantly associated with both OS (HR 0.221, 95% CI 0.128–0.381, p < 0.001) and PFS (HR 0.380, 95% CI 0.242–0.596; p < 0.001). We further integrated PNI into the IPI and PIT prognostic models, and the predictive accuracy of both models was significantly improved.ConclusionPNI is a simple and easily accessible prognostic indicator for AITL.